2001
DOI: 10.1136/ip.7.4.312
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of injury from fighting among adolescent males

Abstract: These findings suggest that injuries associated with fighting are a health risk among adolescent males. Certain behaviors, such as fighting in groups and fighting with strangers, increase the likelihood of injuries requiring medical attention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 13 publications
2
12
0
Order By: Relevance
“…Physical fighting is the most common manifestation of interpersonal violence in adolescence. 1 Although researchers have documented fighting as an obvious and direct cause of adolescent injury, 11 our results support the idea that fighting is a marker for a lifestyle that has inherent injury risks for both boys and girls. In the past, a lifestyle that includes fighting has been described as a behavioral syndrome that can include substance use, truancy, and other problem behaviors during adolescence.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…Physical fighting is the most common manifestation of interpersonal violence in adolescence. 1 Although researchers have documented fighting as an obvious and direct cause of adolescent injury, 11 our results support the idea that fighting is a marker for a lifestyle that has inherent injury risks for both boys and girls. In the past, a lifestyle that includes fighting has been described as a behavioral syndrome that can include substance use, truancy, and other problem behaviors during adolescence.…”
Section: Discussionsupporting
confidence: 73%
“…Similarly, because these findings are based on classroom samples in selected countries, they will not be representative of adolescents in special or nonclassroom settings. Although the obvious link between physical fighting and fighting injury is established, 11 because of sample-size limitations we were unable to study this association, and the etiologic analyses were limited to more common injury outcomes. Finally, although the rates and trends in the occurrence of violence are thought to be representative of the countries under study, they are less likely to depict the experiences of adolescents in other (eg, war-torn 14,15 ) countries.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast with the descriptive data reported, the two papers that analysed injury risk by age of the child found either no differences greater than chance36 or more injuries in younger children 13. Four US cohorts26 3537 reported no statistically significant differences in injury occurrence between different ethnic groups, in contrast with one study from China13 that found more injuries in minority ethnic groups.…”
Section: Resultsmentioning
confidence: 80%